Penerapan Model Example Non-Example dalam Pembelajaran Tema Peduli terhadap Makhluk Hidup Sub Tema Keberagaman Makhluk Hidup - Rojai, Muhamad; Prasetyawati DH, Dwi; Asri Untari, Mei Fita (Universitas Pendidikan Ganesha, 2018)
This reseach aims to knowing how application model Example Non-Example in learning theme Care To Creature Life Sub-Theme Diversity Creature Life In My Evironment Grade IV Lamper Tengah 02 Primary School Semarang. This reseach use type method reaseach quantitative is Pre-experimental desaign with Pretest – Posttest Desaign. Collection data in this reseach with test, observation, and documentation. In sampling wit Purposive Sampling. Result of hypothesis reseach on learning to show thitung = 3,9141 and ttabel with level significant 5% = 2,023, why thitung > ttabel then use model Example Non-Example in learning Theme Care To Creature Life Sub-Theme Diversity Creature Life In My Evironment grade IV Lamper Tengah 02 Primary School Semarang good in learning. Value in pretetst 59,3 in posttest 74,5. While KKM 65. Conclusion model learning Example Non-Example good use in learning Theme Care To Creature Life Sub-Theme Diservisty Creature Life In my Evironment Grade IV Lamper Tengah 02 Primary School Semarang.